Laboratory Diagnosis of von Willebrand's Disease - Mansyur Arif (The Indonesian Biomedical Journal, 2009)
von Willebrand's disease (vWD) is an autosomally inherited bleeding disorder caused by a deficiency or abnormality of von Willebrand factor (vWF). vWF is a multimeric adhesive protein that plays an important role in primary hemostasis by promoting platelet adhesion to the subendothelium at the sites of vascular injury. It is also the carrier of factor VIII (FVIII), thus indirectly contributing to the coagulation process. Bleeding symptoms are usually mucocutaneous and postsurgical with varying severity. The diagnosis of vWD requires a personal and family history of bleeding and confirmation by laboratory analysis involving vWF antigen level, vWF ristocetin cofactor, FVIII activity, ristocetin-induced platelet aggregation, and vWF multimer analysis.KEYWORDS: von Willebrand's disease, von Willebrand factor